IMPLEMENTATION OF ELECTORAL AUTHORITY IN RE-VOTING SELECTION IN 2019 GENERAL ELECTIONS - Busrang Riandy; Laode Husen; Said Sampara (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal